FORCED MARRIAGE PRACTICES IN VILLAGE CIBEUREUM CIAMIS DISTRICT (Study Analysis Of Law No. 23 Of 2004 Concerning Elimination Of Household Violence): Study Analysis Of Law No. 23 Of 2004 Concerning Elimination Of Household Violence - sumadi sumadi; Anis Anjalis (Fakultas Agama Islam Universitas Wiralodra, 2019)
Marriage can be a bridge to the happiness of every culprit, if marriage is based on voluntary, compassionate, mutual protection. But it can also be a bridge of destruction if marriage is done with mere compulsion. The coercion of parents or one of the parents of their children to marry someone whom the child does not want is including psychological violence in the household. Violations of the rights of women in choosing their husbands and mates, which we have often heard is a tyranny, deprives them of their rights, seizes their special decisions, and does not include them in determining the most important choices in their lives.